Complex Cartography: Regulation of E2F Transcription Factors by Cyclin F and Ubiquitin. Issue 8 (August 2020) - Emanuele, Michael J.; Enrico, Taylor P.; Mouery, Ryan D.; Wasserman, Danit; Nachum, Sapir; Tzur, Amit
Abstract : The E2F family of transcriptional regulators sits at the center of cell cycle gene expression and plays vital roles in normal and cancer cell cycles. Whereas control of E2Fs by the retinoblastoma family of proteins is well established, much less is known about their regulation by ubiquitin pathways. Recent studies placed the S kp1-C ul1-F -box-protein (SCF) family of E3 ubiquitin ligases with the F-box protein Cyclin F at the center of E2F regulation, demonstrating temporal proteolysis of both activator and atypical repressor E2Fs. Importantly, these E2F members, in particular activator E2F1 and repressors E2F7 and E2F8, form a feedback circuit at the crossroads of cell cycle and cell death. Moreover, Cyclin F functions in a reciprocal circuit with the cell cycle E3 ligase a naphase-p romoting c omplex/c yclosome (APC/C), which also controls E2F7 and E2F8. This review focuses on the complex contours of feedback within this circuit, highlighting the deep crosstalk between E2F, SCF-Cyclin F, and APC/C in regulating the oscillator underlying human cell cycles. Highlights: Cyclin F is a noncanonical cyclin that targets proteins for ubiquitination and proteasomal degradation via the SCF family of E3 ligases. Transcriptional activators E2F1, E2F2, and E2F3 are substrates of the SCF Cyclin F . Transcriptional repressors E2F7 and E2F8 are substrates of both SCF Cyclin F and APC/C Cdh1 . E2F1 and E2F7/8 and SCF Cyclin F and APC/C Cdh1 regulate each other via negative feedback, highlighting a complex circuit regulating cell cycle transcription.